Law Enforcement against Entrepreneurs who Conduct Criminal Acts to Pay Wages Under the Minimum Wage - Sekar Tresna Raras Tywi; Ira Alia Maerani; Arpangi Arpangi (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2021)
This study aims to determine how law enforcement is carried out by labor inspectors against employers who pay wages lower than the minimum wage. The method used in this paper is sociological juridical. The conclusion of this paper is that law enforcement on the payment of wages below the minimum wage is carried out gradually through preventive educational efforts, repressive nonyustisia to repressive yustisia. It is hoped that through this process the employer can pay the lowest wage according to the minimum wage so that punishment is the last alternative (ultimum remedium).